Thermal behaviour studies of solid state compounds of cinnamylidenepyruvate with trivalent lanthanides and yttrium (III) in an atmosphere of CO2 - Oliviera, JDS de; Fertonani, F. L.; Melios, C. B.; Ionashiro, M. (Editora Unesp, 2002)
Solid state cinnamylidenepyruvate of trivalent lanthanides (except for promethium) and yttrium, were prepared. Thermogravimetry, derivative thermogravimetry (TG, DTG), differential scanning calorimetry (DSC), X-ray diffraction powder patterns and complexometry were used to characterize and to study the thermal behavior of these compounds in a dynamic CO2 atmosphere. The results obtained showed significative differences on the thermal stability and thermal decomposition of these compounds, with regard to the thermal behavior study in a dynamic air atmosphere.
Keywords: lanthanides; yttrium; cinnamylidenepyruvate; CO2 atmosphere; thermal behavior